PENERAPAN PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS DAN SELF-CONFIDENCE SISWA SMK - Hanifah Novianty; Ade Sudrajat; Aflich Yusnita Fitrianna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This research is a class action research (CAR). The aim of the study was to find out, [1] the application of problem-based learning to improve the mathematical reasoning abilities of SMK students [2] the effect of problem-based learning to improve the mathematical reasoning abilities of SMK students. The research was carried out using a qualitative descriptive method and adapted to indicators of mathematical reasoning based on Kemmis and Mc Taggart's analysis. research subjects were 36 students of class XI Multimedia 2 at SMKN 3 Cimahi 2021/2022. Collecting data in this study used observation, tests, self-confidence questionnaires and interviews. From the results of tests and interviews it is known that the basic concept of students' mathematical logic questions initially had errors in solving the problems, but there was an increase in each cycle. The results of data on mathematical reasoning ability affect the average percentage of the self-confidence questionnaire which tends to be high, namely score 4 of 25%, score 3 of 19.4%, score 2 of 31.7% and score 1 of 7.9%, so the conclusion is that the mathematical reasoning abilities of SMK students belong to the medium category.